2020
DOI: 10.1002/rco2.24
|View full text |Cite
|
Sign up to set email alerts
|

Janus kinase inhibitors suppress cancer cachexia‐associated anorexia and adipose wasting in mice

Abstract: Background Cachexia, a syndrome of muscle atrophy, adipose loss, and anorexia, is associated with reduced survival in cancer patients. The colon adenocarcinoma C26c20 cell line secretes the cytokine leukaemia inhibitory factor (LIF), which induces cachexia. We characterized how LIF promotes cachexia-associated weight loss and anorexia in mice through Janus kinase (JAK)dependent changes in adipose and hypothalamic tissues. Methods Cachexia was induced in vivo with the heterotopic allotransplanted administration… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 36 publications
(51 reference statements)
4
49
0
Order By: Relevance
“…The adipocyte fractions were subjected to qRT-PCR, and Adipoq-Cre;LIFR fl/fl adipocytes demonstrated no detectable mRNA expression of LIFR , verifying disruption of the gene in adipocytes in the adipose tissue of the knockout animals ( Figure 1 C). Adipocytes from the LIFR knockout mice also had a significant decrease in IL6 expression compared with littermate controls, which is consistent with our previous findings that LIF increases IL6 expression in a JAK-dependent manner in differentiated adipocytes ( Arora et al., 2020 ). At the protein level, there was a significant reduction in LIFR-α in eWAT of knockout mice compared with controls, with equivalent hepatic levels of LIFR-α in knockout and littermate controls ( Figure 1 D).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The adipocyte fractions were subjected to qRT-PCR, and Adipoq-Cre;LIFR fl/fl adipocytes demonstrated no detectable mRNA expression of LIFR , verifying disruption of the gene in adipocytes in the adipose tissue of the knockout animals ( Figure 1 C). Adipocytes from the LIFR knockout mice also had a significant decrease in IL6 expression compared with littermate controls, which is consistent with our previous findings that LIF increases IL6 expression in a JAK-dependent manner in differentiated adipocytes ( Arora et al., 2020 ). At the protein level, there was a significant reduction in LIFR-α in eWAT of knockout mice compared with controls, with equivalent hepatic levels of LIFR-α in knockout and littermate controls ( Figure 1 D).…”
Section: Resultssupporting
confidence: 92%
“…We have now shown that LIF signals through its receptor LIFR-α to induce STAT3 activation and adipocyte lipolysis in adipose. We previously showed that LIF and other IL-6 family members increase the lipolysis potential of the adipocyte through a JAK-dependent mechanism ( Arora et al., 2020 ). Although we observed an association of STAT3 phosphorylation with LIF and IL-6-mediated lipolysis, there was no evidence that STAT3 was required for IL-6 family cytokine-mediated adipocyte lipolysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This, in turn, results in cachexia-associated adipose wasting as well as anorexia. The authors noted that the use of JAK inhibitors in both in vitro and in vivo models of CC inhibits this process [ 74 ].…”
Section: Systemic Inflammatory Response In Colorectal Cancer-assocmentioning
confidence: 99%